Identifying Criminals’ Risk Preferences - Klick, Jonathan (2016)
There is a 250 year old presumption in the criminology and law enforcement literature that people are deterred more by increases in the certainty rather than increases in the severity of legal sanctions. We call this presumption the Certainty Aversion Presumption (CAP). Simple criminal decision making models suggest that criminals must be risk-seeking if they behave consistently with CAP. This implication leads to disturbing interpretations, such as criminals being categorically different than law abiding people, who often display risk-averse behavior while making financial decisions. Moreover, policy discussions that incorrectly rely on criminals’ risk attitudes implied by CAP are ill-informed, and may therefore have unintended negative consequences. In this article, we first demonstrate, contrary to most of the existing literature, that CAP consistent behavior does not imply risk-seeking behavior. A host of considerations that are unrelated to risk-attitudes can generate behavior that is consistent with CAP, including stigmatization; discounting; judgment proofness; the forfeitability of illegal gains; and the possibility of being punished for unsuccessful criminal attempts. Next, we discuss empirical methods that can be employed to gain a better understanding of criminals’ risk-attitudes and responsiveness to various punishment schemes. These methods focus on the various non-risk-related-considerations that may be responsible for CAP consistent behavior. Finally, we discuss the importance of gaining a better understanding of criminals’ attitudes for purposes of designing optimal law enforcement methods, punishment schemes for repeat offenders, plea bargaining procedures and standards of proof